Bacterial Growth And Diesel Biodegradation In The Presence Of As, Cu And Pb By Antarctic Marine Bacteria - Zakaria, N.N.; Roslee, A.F.A.; Zulkharnain, A.; Gomez Fuentes, Claudio German; Abdulrasheed, M.; Sabri, S.; Calisto Ulloa, Nancy Cristina; Ahmad, S.A. (My University, 2019)
Antarctica is considered to be low-impacted by anthropogenic activities despite the rising activities occurring in the Southern Ocean. Rising human activities from within Antarctica and external sources resulted in hydrocarbon and heavy metal pollution and create more and more evidence on how much anthropogenic pollution has influenced the southern polar region. Bioremediation possibilities in these parts are very limited in terms of maximum efficiency due to its unique climatic conditions. Furthermore, heavy metals come hand in hand with hydrocarbon pollution and there is a call to obtain. In the present study, diesel degradation was inhibited the most by Pb (31.75%), As (34.35%) and lastly Cu (48.91%) in comparison to control flask (65.19%). Bacterial growth was most inhibited by Cu. Pb had little effect to the growth of bacteria in comparison to As and Cu. Growth rates were obtained by fitting the Exponential mathematical model to the data and obtaining individual growth rates and measures of good fit. ANOVA analysis of the growth obtained P values of control, As and Pb to be <0.05 while Cu gave a P>0.05. © 2019 Malaysian Society for Biochemistry and Molecular Biology. All rights reserved.
Keywords: Antarctica; Diesel; Exponential Growth; Heavy Metal; Marine